Społeczne determinanty rozwoju twórczej wyobraźni w ujęciu kulturowo- -historycznym – wybrane aspekty - Gąsiorek, Przemysław (Studia Edukacyjne, 2021)
In this article, I analyze the social determinants of the development of creative imagination. Due to its importance, this phenomenon is one of the main areas of research in pedagogy and psychology, which, however, despite numerous analyzes, has not been sufficiently explained. One interpretation of the understanding of imagination as a social mental activity is outlined here. This approach is presented mainly in the works of L.S. Vygotski and his students. Their analyses go beyond the mechanical understanding of the imagination and the dualistic division of the imagined and real worlds. The cultural-historical theory of the development of creative imagination describes it as an internalized system of social relations. The development of this form of imagination, according to Vygotsky, is the main goal of human development. The most effective way to achieve it is education, which “nurtures” in the child all manifestations of a socially creative imagination.